The MacSharry reforms of the Common Agricultural Policy: a challenge to public choice theory - Kay, Adrian (1997)
This thesis draws on the insights of economics, political economy and political science to study the MacSharry reforms of the CAP enacted in May 1992. It has two objectives. First, to understand the MacSharry reforms in terms of why they happened, when they did and in the form that they did. Second, to develop a more general framework for the interpretation of CAP reforms.